2022
DOI: 10.5534/wjmh.210155
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Re-Uptake Inhibitors for Premature Ejaculation in Adult Men: A Cochrane Systematic Review

Abstract: Purpose Selective serotonin re-uptake inhibitors (SSRIs) are frequently used to treat premature ejaculation (PE) in men. We performed a Cochrane review to assess the efficacy of SSRI treatment for PE. Materials and Methods We extensively searched a range of databases up to May 2020 and only included randomized controlled trials. Results A total of 31 studies with 8,254 men were included in this analysis. We found that SSRI treatment probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this regard, the rapid ejaculation displayed by male rats in MPCA conditions resembles acquired premature ejaculation in men, which is often influenced by the presence of anxiety or stressful factors during sexual intercourse. [1][2][3]14 Another important parameter of male sexual behavior to analyze is the number of intromissions preceding ejaculation, as it plays a role in the rat's ejaculatory threshold. 24 Our results demonstrated that fluoxetine caused a significant increase (p < 0.05) in the number of intromissions at a dose of 10 mg/kg, compared to saline, which was not observed in the sertraline group at the same dose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, the rapid ejaculation displayed by male rats in MPCA conditions resembles acquired premature ejaculation in men, which is often influenced by the presence of anxiety or stressful factors during sexual intercourse. [1][2][3]14 Another important parameter of male sexual behavior to analyze is the number of intromissions preceding ejaculation, as it plays a role in the rat's ejaculatory threshold. 24 Our results demonstrated that fluoxetine caused a significant increase (p < 0.05) in the number of intromissions at a dose of 10 mg/kg, compared to saline, which was not observed in the sertraline group at the same dose.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,8,[10][11][12][13] The treatment for premature ejaculation currently uses SSRIs, which increase the synaptic levels of this neurotransmitter. 14 It is assumed that the ejaculatory process inhibition is due to their effect on the 5-HT2C receptor. [5][6][7][8] Additionally, dapoxetine is the primary SSRIs employed for premature ejaculation treatment but has disadvantages such as cost and potential side effects for some men.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations